2019
DOI: 10.1136/bmjspcare-2018-001761
|View full text |Cite
|
Sign up to set email alerts
|

Imminent death: clinician certainty and accuracy of prognostic predictions

Abstract: ObjectivesTo determine the accuracy of predictions of dying at different cut-off thresholds and to acknowledge the extent of clinical uncertainty. Design Secondary analysis of data from a prospective cohort study. setting An online prognostic test, accessible by eligible participants across the UK. Participants Eligible participants were members of the Association of Palliative Medicine. 99/166 completed the test (60%), resulting in 1980 estimates (99 participants × 20 summaries). Main outcome measures The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…(5). 4 The General Medical Council guidance recogniseizes that the benefit, burdens and risks associated with artificial hydration and nutrition are not clear cut, acknowledging that patients may can experience distressing symptoms because of inadequate hydration (or nutrition), but also that attempts to meet the perceived need for hydration (and nutrition) may can in itself cause avoidable suffering. (5).…”
Section: Nutrition and Hydrationmentioning
confidence: 99%
“…(5). 4 The General Medical Council guidance recogniseizes that the benefit, burdens and risks associated with artificial hydration and nutrition are not clear cut, acknowledging that patients may can experience distressing symptoms because of inadequate hydration (or nutrition), but also that attempts to meet the perceived need for hydration (and nutrition) may can in itself cause avoidable suffering. (5).…”
Section: Nutrition and Hydrationmentioning
confidence: 99%
“…Delivering five priorities guided care can often be challenging for teams not familiar with this. 7 Previous efforts had resulted in multiple fragmented and underutilised paper documents and areas of poor performance. It was initially acknowledged by the project team that a multidisciplinary care plan for people at the end of their lives would serve a multitude of purposes.…”
Section: Before the Covid-19 Pandemicmentioning
confidence: 99%
“…As a result, end-of-life care is often being provided by those less familiar with the nuances of this, and specialist palliative care teams need to respond by adjusting the assistance they offer through review of their activity and resources. 7,8 People less experienced or comfortable in delivering care for patients who are dying may find conversations about this more difficult and require support. 1 Having earlier identified that document redesign, the provision of clear guidance and ongoing review of this could support staff in providing individualised care at the end of a person's life, a further PDSA cycle was commenced.…”
Section: During the Covid-19 Pandemicmentioning
confidence: 99%
“…We can be both under- and overoptimistic, but we tend towards the former. And more senior doctors aren’t necessarily more accurate 11…”
Section: Major Variationsmentioning
confidence: 99%